One-Pot Microwave-Assisted Intramolecular Rearrangement of Pyranone Amide to Pyridone Ester - Mishra, Uttam Kumar; Kumar, Rajan; Jha, Ashok Kumar; Bal, Chandralata; Sharon, Ashoke (Synthesis, 2024)
This investigation presents a novel, cost-effective approach for creating a 2-pyridone core substituted with an ester group through intramolecular rearrangement. This one-step transformation involves an amide-mediated intramolecular transformation of a pyranone to pyridone scaffold, followed by alcoholic-mediated ester formation, in 75–85% yield. Deuterated alcohol was used to confirm the esterification under alcoholic conditions. The reaction requires a nucleophile source from the solvent, which was observed by performing the reaction of three derivatives in CD3OD to obtain the desired carboxylate compounds, replacing -OR with -OCD3. All synthesized compounds were characterized by spectroscopic analysis, and six selected compounds were further confirmed by single-crystal X-ray diffraction studies.
Keywords: microwave-assisted method; alcoholic conditions; intramolecular rearrangement; pyranones; pyridones; ORTEP